Patients' Technology Readiness and eHealth Literacy: Implications for Adoption and Deployment of eHealth in the COVID-19 Era and Beyond. Issue 4 (2nd April 2022) - Lee, Wan Ling; Lim, Zi Jing; Tang, Li Yoong; Yahya, Nor Aziyan; Varathan, Kasturi Dewi; Ludin, Salizar Mohamed
Abstract : The COVID-19 pandemic has rerouted the healthcare ecosystem by accelerating digital health, and rapid adoption of eHealth is partly influenced by eHealth literacy (eHL). This study aims to examine patients' eHL in relation to their "technology readiness"—an innate attitude that is underexplored in clinical research. A total of 276 adult inpatients with hypertension, diabetes mellitus, and coronary heart disease were surveyed cross-sectionally in 2019 using self-reported questionnaires: eHealth Literacy Scale and Technology Readiness Index (2.0). The study found moderate eHL (mean, 27.38) and moderate technology readiness (mean, 3.03) among patients. The hierarchical regression model shows that lower eHL scores were associated with patients of minor ethnicity (Malaysian Chinese), with an unemployed status, and having >1 cardiovascular risk (β = −0.136 to −0.215, R 2 = 0.283, P s < .005). Technology readiness is a strong determinant of eHL (Δ R 2 = 0.295, P < .001) with its subdomains (optimism, innovativeness, and discomfort) significantly influencing eHL (|β| = 0.28-0.40, P s < .001), except for the insecurity subdomain. Deployment of eHealth interventions that incorporate assessment of patients' eHL and technology readiness will enable targeted strategies, especially in resource-limited settings hit hard by the pandemic crisis.